Assembling land for urban revitalization in the presence of linchpin parcels and information asymmetries: An experimental investigation. (December 2020) - Zillante, Artie; Read, Dustin C.; Seiler, Michael J.
Abstract: This study uses economic experiments to determine if information asymmetries are likely to frustrate government efforts to assemble land for urban revitalization when there is a linchpin parcel that must be acquired to move a development project forward. Results suggest holdout behavior is more pronounced when landowners know a linchpin parcel exists. Surprisingly, landowners who know they control such parcels are found to be more willing to sell than those who are uncertain about the strategic importance of their properties. These observations raise interesting questions about the nature of holdout problems and how they can potentially be overcome by approaching land assembly in a transparent manner.